Working life expectancies among individuals with type 1 and type 2 diabetes over a 30-year period - Nexø, Mette A.; Pedersen, Jacob; Cleal, Bryan; Andersen, Ingelise; Bjørner, Jakob B. (Scandinavian Journal of Work, Environment & Health, 2021)
' ' OBJECTIVES ': 'This study aimed to (i) estimate working life expectancies (WLE) and the number of working years lost (WYL) among individuals with type 1 and type 2 diabetes over a 30-year period and (ii) identify educational differences in WLE and WYL. ' ' METHODS ': 'Individuals aged 18–65 years diagnosed with type 1 (N=33 188) or type 2 diabetes (N=81 930) in 2000–2016 and age- and gender-matched controls without diabetes (N=663 656) were identified in Danish national registers. WLE in years were estimated as time in employment from age 35–65 years. We used a life-table approach with multi-state (eg, disability pension, sickness absence, unemployment) Cox proportional hazard modeling. Analyses were performed separately for sex, cohabitation status, educational duration, and type of diabetes. Inverse probability weights accounted for differences between populations. ' ' RESULTS ': 'People with diabetes had significantly shorter WLE and greater WYL compared to people without diabetes over the 30-year span. At age 35, cohabitant women with lower education and diabetes lost up to 8.0 years [95% confidence interval (CI) 5.0–11.0] and men 7.0 years (95% CI 4.0–8.7). WYL among women with higher education was 4.4 (95% CI 6.6–2.3) and 3.7 years among men (95% CI 1.5–4.5). Compared to people with type 2 diabetes, those with type 1 spend significantly more years in disability pension, but there were no significant differences in the other WYL estimates. ' ' CONCLUSIONS ': 'The WYL among people with diabetes is substantial and characterized by social disparities. The WYL help identify intervention targets at different ages, types of diabetes, sex, educational and cohabitant status.
Keywords: cohort study; diabetes; epidemiology; occupational health; type 2 diabetes; work life expectancy; working life expectancy; working years lost